Comparison of in vivo effects of calcitonin, risedronate and raloxifene on erythrocyte antioxidant enzyme activity, lipid peroxidation and nitric oxide in postmenopausal osteoporosis - Ozgocmen, S.; Kaya, H.; Fadillioglu, E.; Yilmaz, Z. (B M J Publishing Group, 2006)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2006) -- JUN 21-24, 2006 -- Amsterdam, NETHERLANDS